Clinical Analysis of the HBV Infection Status of 135 Patients with Diffuse Large B Cell Lymphoma Treated with R-CHOP or CHOP/CHOP-Like Chemotherapy - Guo, Wei (PLoS One, 2015)
OBJECTIVES: This study aimed to determine the HBV infection status of 135 patients with DLBCL (diffuse large B cell lymphoma), to analyze the overall survival (OS) and progression-free survival (PFS) of the different HBV infection status groups, and to discuss the relationship between HBV serological test results and the prognosis of DLBCL patients. METHODS: A retrospective analysis was performed of the clinical data, HBV serological test results, and PFS/OS of 135 DLBCL patients who were initially diagnosed and treated with more than 3 cycles of an R-CHOP/CHOP/CHOP-like regimen at our center from January 1, 2008 to December 31, 2012. RESULTS: The patients in the HBV infection group were older at disease onset (≥60 years old) and were more likely to present with stage 3-4 disease compared with the HBV-free group (P = 0.030 and P = 0.025, respectively). Approximately 50% of the patients with an active HBV infection required a reduction in the chemotherapy dose, and 66.7% of the patients in this group received more than 1 line of therapy; these rates were significantly higher than those in the no infection group (P = 0.003 and P = 0.011, respectively). Although HBV infection had no obvious influence on the outcome of first-line therapy, patients with an inactive infection had a higher relapse/progression rate within 3 months after a CR/PR than patients with an active infection (14/20 vs. 1/12, P = 0.001). The PFS at 1 year, 3 years and OS rates at 1 year, 3 years were significantly lower in the active HBV infection group than in the HBV-free group (P = 0.008, P = 0.002, P = 0.004, and P = 0.002, respectively). The PFS rates at 1 year and 3 year in HBV-free group were higher than those in the HBV infection group (80.5% and 52.9% P = 0.001, 78.1% and 44.4% P = 0.002). The lymphoma-related mortality rates were 2.7% in the no infection group, 19.2% in the HBV infection group (P = 0.004), and 28.6% in the active HBV infection group (P = 0.001). Among the patients treated with MabThera, the PFS in the HBV infection group was 11 months in the HBV infection group and 67 months in the infection-free group (P = 0.000). A Cox regression model of PFS revealed that age ≥60 years and HBV infection were independent prognostic factors (age: P = 0.019, HR = 2.002, 95% CI 1.123-3.567; HBV infection: P = 0.026, HR = 0.494, 95% CI 0.265-0.919). CONCLUSION: Compared with the patients in HBV-free group, those in the HBV infection group were older at disease onset, and the active infection patients presented with more advanced disease and had a lower PFS at 1, 3 years as well as a lower OS at 3 years. The patients in the inactive infection group had a higher progression/relapse rate within 3 months after a CR/PR than those in the active infection group. HBV infection was an unfavorable factor for PFS in the MabThera group. An age ≥60 years and HBV infection were independent unfavorable prognostic factors for PFS.